Patterns of bruising in preschool children with inherited bleeding disorders: a longitudinal study. Issue 12 (22nd July 2016) - Collins, Peter W; Hamilton, Melinda; Dunstan, Frank D; Maguire, Sabine; Nuttall, Diane E; Liesner, Ri; Thomas, Angela E; Hanley, John; Chalmers, Elizabeth; Blanchette, Victor; Kemp, Alison M
Abstract : Objective: The extent that inherited bleeding disorders affect; number, size and location of bruises in young children <6 years. Design: Prospective, longitudinal, observational study. Setting: Community. Patients: 105 children with bleeding disorders, were compared with 328 without a bleeding disorder and classified by mobility: premobile (non-rolling/rolling over/sitting), early mobile (crawling/cruising) and walking and by disease severity: severe bleeding disorder factor VIII/IX/XI <1 IU/dL or type 3 von Willebrand disease. Interventions: Number, size and location of bruises recorded in each child weekly for up to 12 weeks. Outcomes: The interventions were compared between children with severe and mild/moderate bleeding disorders and those without bleeding disorders. Multiple collections for individual children were analysed by multilevel modelling. Results: Children with bleeding disorders had more and larger bruises, especially when premobile. Compared with premobile children without a bleeding disorder; the modelled ratio of means (95% CI) for number of bruises/collection was 31.82 (8.39 to 65.42) for severe bleeding disorders and 5.15 (1.23 to 11.17) for mild/moderate, and was 1.81 (1.13 to 2.23) for size of bruises. Children with bleeding disorders rarely had bruises on the ears, neck, cheeks, eyes or genitalia. Conclusions: Children with bleeding disorder have more and larger bruises at all developmental stages. The differences were greatest in premobile children. In this age group for children with unexplained bruising, it is essential that coagulation studies are done early to avoid the erroneous diagnosis of physical abuse when the child actually has a serious bleeding disorder, however a blood test compatible with a mild/moderate bleeding disorder cannot be assumed to be the cause of bruising.